Densification behavior and properties of iron oxide doped Y-TZP ceramics - Siva Kumar, S.; Teow, L. H.; Ali, Niakan; K. C. L., Jeffery (School of Engineering,Taylor’s University, 2016)
The effect of small addition of Fe2O3 (up to 1 wt%) on the densification behaviour and mechanical properties of commercially available 3 mol% Yttria Tetragonal Zirconia Polycrystals (Y-TZP) sintered from 1250°C to 1500°C was investigated. Tests were carried out in order to determine the bulk density, Vickers hardness, Young’s Modulus and fracture toughness of the sintered samples. Based on the work carried out, it is revealed that the amount of dopants and sintering temperature influences the mechanical properties of YTZP. The results showed that even sintering at low temperature at 1250°C, relative bulk density ~98% of theoretical density could be achieved with the addition of 0.3 wt% Fe2O3 . The additions of small amounts of Fe2O3 from 0.05 wt% to 1.0 wt% was found to be beneficial in enhancing the matrix stiffness and hardness of the sintered bodies when compared to the undoped counterpart sintered at same temperature. However, the fracture toughness was found to be unaffected by the additions of small dopant amounts except for the case of 0.5 and 1 wt% Fe2O3 when sintered above 1400°C.